2022
DOI: 10.3390/diagnostics12020274
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Deep Learning and Conventional Machine Learning in Classifying Iliofemoral Deep Venous Thrombosis upon CT Venography

Abstract: In this study, we aimed to investigate quantitative differences in performance in terms of comparing the automated classification of deep vein thrombosis (DVT) using two categories of artificial intelligence algorithms: deep learning based on convolutional neural networks (CNNs) and conventional machine learning. We retrospectively enrolled 659 participants (DVT patients, 282; normal controls, 377) who were evaluated using contrast-enhanced lower extremity computed tomography (CT) venography. Conventional mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…It was clear that the DL models had better performance than the radiomics-based ML model in differentiating ASPs from SPs (AUC = 0.9294 vs. AUC = 0.8853). These results were consistent with the findings for Mantle Cell Lymphoma ( 27 ) and Deep Vein Thrombosis ( 28 ) that DL models had better diagnostic performance than radiomics-based ML models. This was due to the fact that DL extracts more representative high-level abstract features from the raw data, while machine learning requires manual feature selection and design.…”
Section: Discussionsupporting
confidence: 91%
“…It was clear that the DL models had better performance than the radiomics-based ML model in differentiating ASPs from SPs (AUC = 0.9294 vs. AUC = 0.8853). These results were consistent with the findings for Mantle Cell Lymphoma ( 27 ) and Deep Vein Thrombosis ( 28 ) that DL models had better diagnostic performance than radiomics-based ML models. This was due to the fact that DL extracts more representative high-level abstract features from the raw data, while machine learning requires manual feature selection and design.…”
Section: Discussionsupporting
confidence: 91%
“…The first study aimed to investigate quantitative differences between with region of deep venous with and without DVT by classifying the region of deep vein. This formative study indicated that the CNN model can extract useful features that can distinguish the region containing DVT from other regions 12 . However, the result of the study did not include information about localization of the DVT in LECTA.…”
Section: Introductionmentioning
confidence: 88%
“…Imaging modalities for DVT diagnosis include ultrasonography (US), computed tomography angiography of the bilateral lower extremities (LECTA), magnetic resonance imaging (MRI), and catheter venography. To overcome the limitations of the DVT manual analysis, studies have been conducted using various imaging modalities and have shown the potential and efficiency of an AI-based CAD system for DVT diagnosis 8 12 . Among the image modalities, LECTA was found to be more advantageous—it provided more objective images than US; it is easily accessible and frequently used to provide information about extravascular tissues in the bilateral lower extremities and abdominopelvic region.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Similarly, ML-based tools have been developed for computer-aided diagnosis of DVT, although the majority utilize MR/CE-MRI or CT-venography, while the most widely employed diagnostic technique is compression ultrasound. [45][46][47][48] Aiming to equip non-specialists to detect DVT, a deep learning approach to compression ultrasound images was developed and externally validated with a negative predictive Bleeding, Thrombosis and Vascular Biology 2024; 3(s1):123 value of 98-99%. The authors also performed a cost analysis of integrating this ML tool into their current diagnostic pathway and estimated the net monetary benefits.…”
Section: Machine Learning Applications For Image Recognition In Venou...mentioning
confidence: 99%